PEMBINAAN KARAKTER SISWA MELALUI PEMBIASAAN SHALAT DHUHA DI SMKN 5 KOTA MALANG - Alimatus Sa’diyah; Abdul Jalil; Mutiara Sari Dewi (VICRATINA, 2020)
Character education is the process of providing guidance to students to become human beings who have character in the defcontent of hearts, thinking, body and taste. Character education is one of the fortresses needed in a moral fix. In Islamic religion, character education has been implemented early, one of them is the prayer Dhuha. Character building through this dhuha prayer media is character education to overcome moral degradation, mindset, and behavior of students. In order to realize the above purpose of research is done with qualitative research. The data collection procedure is done using the observation method, which is direct observation of the target, interview method, which is the method of data collection by oral question and answer with research source, and the method of documentation that is process of searching data about matters related to the research. The results showed that the character development that was done in SMKN 5 Malang is through Dhuha prayer media that is employed by students and teachers. While the value of character developed is a religious that is reflected in some behavior or actions of students such as doing Dhuha prayers continuously, The discipline that reflects the order of orderly behavior and adherent to various provisions and regulations, honest reflected in the movement and recitation of prayer Dhuha, Responsibility that is reflected in the awareness to carry out the duties of Dhuha prayer and obligation well unresorted.